Does Cross-Country Income Convergence Occur? - Thoifur, Ahmad (Universitas Muhammadiyah Ponorogo, 2025)
Income is one of the most popular dimensions for measuring welfare and development; hence, comparing welfare and well-being among countries can be conducted by comparing their per capita income. While income convergence is a certain implication in neoclassical growth theory, it does not always occur empirically. This study aims to investigate whether income convergence occurs among economies. Employing data from 93 countries from 1980 to 2022 obtained from the World Bank, the two-way fixed effect panel model is implemented to verify the existence of Î²-convergence. The result shows that the initial per capita gross domestic product, representing income, negatively affects income growth, indicating that Î²-convergence occurs in terms of global and club convergence. This implies that poor countries grew faster than affluent countries. After Î²-convergence is confirmed, Ïƒ-convergence is analyzed by measuring the income dispersion across countries over time. Ïƒ-convergence exists if the dispersion declines as time passes. The result shows that Ïƒ-convergence exists only among G20, OECD, lower-middle-income, higher-middle-income, and high-income countries. This fact implies that the income gap between poor and rich countries within those groups shrinks over time. In contrast, the income gap among low-income countries did not experience a significant decline during the period. Therefore, international organizations and partnerships must pay more attention to and assist lower-income countries to achieve higher growth rates.